The galactic bulge exploration: V. the secular spherical and X-shaped Milky Way bulge - Prudil, Zdeněk; Debattista, V. P.; Silva, L. Beraldo e; Anderson, S. R.; Gough-Kelly, S.; Kunder, A.; Rejkuba, M.; Gerhard, O.; Wyse, R. F. G.; Koch-Hansen, Andreas; Rich, R. M.; Savino, Alessandro (Astronomy and astrophysics, 2025)
In this work, we derive systemic velocities for 8456 RR Lyrae stars. This is the largest dataset of these variables in the Galactic bulge to date. In combination with Gaia proper motions, we computed their orbits using an analytical gravitational potential similar to that of the Milky Way (MW) and identified interlopers from other MW structures, which amount to 22% of the total sample. Our analysis revealed that most interlopers are associated with the halo, and the remainder are linked to the Galactic disk. We confirm the previously reported lag in the rotation curve of bulge RR Lyrae stars, regardless of the removal of interlopers. The rotation patterns of metal-rich RR Lyrae stars are consistent with the pattern of nonvariable metal-rich giants, following the MW bar, while metal-poor stars rotate more slowly. The analysis of the orbital parameter space was used to distinguish bulge stars that in the bar reference frame have prograde orbits from those on retrograde orbits. We classified the prograde stars into orbital families and estimated the chaoticity (in the form of the frequency drift, log ΔΩ) of their orbits. RR Lyrae stars with banana-like orbits have a bimodal distance distribution, similar to the distance distribution seen in metal-rich red clump stars. The fraction of stars with banana-like orbits decreases linearly with metallicity, as does the fraction of stars on prograde orbits (in the bar reference frame). The retrograde-moving stars (in the bar reference frame) form a centrally concentrated nearly spherical distribution. From analyzing an N-body+SPH simulation, we found that some stellar particles in the central parts oscillate between retrograde and prograde orbits and that only a minority stays prograde over a long period of time. Based on the simulation, the ratio of prograde and retrograde stellar particles seems to stabilize within some gigayears after the bar formation. The nonchaoticity of retrograde orbits and their high numbers can explain some of the spatial and kinematical features of the MW bulge that have been often associated with a classical bulge.